Improved magnetic resonance myelography of the lumbar spine using image fusion and volumetry - Eberhardt, Knut; Ganslandt, Oliver Thomas; Stadlbauer, Andreas (Journal of Neurosurgery-Spine, 2014)
The goal of this study was to investigate the usefulness and diagnostic potential of an improved MR myelography approach using a dedicated, heavily T2-weighted, 3D MRI sequence in combination with image fusion. A further aim was to compare dural areas and volumes of normal and pathological altered lumbar spine levels, and accuracy in the assessment of the stenoses, with those obtained by postmyelographic CT.Fifty patients underwent myelography, postmyelographic CT, and the improved MR myelography approach using a dedicated, heavily T2-weighted, 3D MRI sequence and image fusion. Dural cross-sectional areas and volumes for normal lumbar levels and levels with stenosis were calculated for postmyelographic CT and MR myelography data. The significant differences and Pearson correlations between dural cross-sectional areas and volumes from L1-2 to L5-S1 of postmyelographic CT and MR myelography were analyzed. The 99% CIs for normal and stenotic levels in patients with claudication distances less than 100 meters were calculated.For both dural areas and volumes in normal lumbar levels, the authors found no significant differences and strong correlations between postmyelographic CT and MR myelography. For the lower lumbar levels (L4-5 and L5-S1) they found significantly larger dural areas on MR myelography compared with postmyelographic CT, but not for the upper levels (L2-3 and L3-4). Dural volume analysis revealed significantly larger volumes for MR myelography at all 4 lumbar levels with stenoses in the cohort (L2-3 to L5-S1). Complete separation with no overlap was found between the 99% CIs for normal levels and stenotic levels.Differences in dural areas and volumes in this study may have been caused by the fact that in the case of a severely compressed thecal sac, the viscosity of the intrathecally applied contrast agent is too high in the framework of myelography. The gravitationally dependent component is thus too low to achieve sufficient fluid contrast. An optimized MR myelography approach-a dedicated 3D MR myelography sequence with high spatial resolution in combination with image fusion-is required to achieve a more reliable diagnosis of lumbar spine stenoses, especially with severe compression, compared with postmyelographic CT. This MR myelography approach may be helpful in preventing overestimation of lumbar spine stenoses. The upper limits of 99% CIs for stenotic levels can be interpreted as an indication for surgical treatment. However, further studies that include postoperative outcomes are required.
EVALuna2:22867